1988
DOI: 10.1128/jb.170.4.1783-1788.1988
|View full text |Cite
|
Sign up to set email alerts
|

Absence of autolytic activity (peptidoglycan nicking) in penicillin-induced nonlytic death in a group A streptococcus

Abstract: The extent of sublytic autolysin activity (peptidoglycan [PG] nicking) after exposure of exponentially growing cultures of a group A streptococcus (GAS) to benzylpenicillin (PenG) was studied by determining changes in the glycan chain length of PG polymers. The average PG chain length in isolated cell walis was estimated by calculating the ratio of the total hexosamine content (Morgan-Elson-reactive material) A unified model for the action of inhibitors of cell wall synthesis (21, 26) predicts that in all s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
1

Year Published

1989
1989
2015
2015

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 24 publications
0
12
1
Order By: Relevance
“…The concurrence of cell death and lysis in these bacteria has led to the widely held belief that the cause of cell death is the suicidal (unregulated) activity of autolytic enzymes. On the other hand, it is also known that in certain species of bacteria penicillin can have powerful bactericidal activity without accompanying autolysis (10,13,18), suggesting that mechanisms other than cell lysis may exist in bacteria for the killing effect of penicillin.In order to clarify the relationship between penicillininduced lysis and killing in pneumococci, we performed a series of experiments using autolysis-inhibiting agents and pneumococcal autolysin mutants carrying a variety of defects in the structural determinant (IytA) of the major autolysin (an N-acetylmuramoyl-L-alanine amidase; referred to as amidase). We also characterized in detail a recently described (19) new type of mutation (cid) that drastically reduces penicillin-induced killing in both wild-type (Lyt+) cells and Lyt-mutants of pneumococci.…”
mentioning
confidence: 99%
“…The concurrence of cell death and lysis in these bacteria has led to the widely held belief that the cause of cell death is the suicidal (unregulated) activity of autolytic enzymes. On the other hand, it is also known that in certain species of bacteria penicillin can have powerful bactericidal activity without accompanying autolysis (10,13,18), suggesting that mechanisms other than cell lysis may exist in bacteria for the killing effect of penicillin.In order to clarify the relationship between penicillininduced lysis and killing in pneumococci, we performed a series of experiments using autolysis-inhibiting agents and pneumococcal autolysin mutants carrying a variety of defects in the structural determinant (IytA) of the major autolysin (an N-acetylmuramoyl-L-alanine amidase; referred to as amidase). We also characterized in detail a recently described (19) new type of mutation (cid) that drastically reduces penicillin-induced killing in both wild-type (Lyt+) cells and Lyt-mutants of pneumococci.…”
mentioning
confidence: 99%
“…On the basis of previous studies, it was suggested that the tolerance might be due to alterations in bacterial autolysis, because killing of nontolerant bacteria was often accompanied by massive cell lysis (6). However, penicillin has been shown to kill pathogens such as Streptococcus pyogenes and Enterococcus hirae efficiently without inducing significant lysis of the cells (7)(8)(9). Furthermore, suppression of autolysis in Streptococcus pneumoniae and Staphylococcus aureus had no significant effect on killing by penicillin (6,(10)(11)(12)(13).…”
mentioning
confidence: 99%
“…Moreover, unlike pneumococci, S. gordonii is not lysed during beta-lactam therapy. This allows an analysis that is more restricted to autolysis-independent mechanisms of penicillin-induced killing and penicillin tolerance (13,25).…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies indicated that autolysis is not the sole mechanism of penicillin-induced killing. Certain bacteria, such as Streptococcus pyogenes and other gram-positive cocci, are killed extensively by penicillin in spite of the fact that they are not lysed by the antibiotic (6,14,25). Moreover, specific blockage of penicillin-induced lysis in Streptococcus pneumoniae and Staphylococcus aureus decreased drug-induced killing only marginally, thus suggesting that other, autolysis-independent pathways were involved in penicillin-induced lethality (11,13,26,31,36,37).…”
mentioning
confidence: 99%